Bibliometric analysis of research trends on hyperbaric oxygen therapy in stroke from 2000 to 2022 - Zhou, Mei; Chen, Xinxin; Li, Dan; Luo, Jiao; Song, Sihui; You, Jiuhong; Ma, Hui; Huang, Cheng (Frontiers in Neurology, 2025)
BackgroundStroke primarily results from the interruption of cerebral blood flow. Hyperbaric oxygen therapy (HBOT), a noninvasive and promising therapeutic intervention, has been widely used to treat various ischemic and hypoxic conditions. Over the past two decades, extensive research has demonstrated HBOT's efficacy in reducing cerebral infarct volume, establishing it as a viable neuroprotective strategy. Given these findings, this study employs bibliometric analysis to explore emerging trends and key research foci in HBOT applications for stroke management.MethodWe performed a systematic literature search on hyperbaric oxygen therapy (HBOT) and stroke using the Web of Science Core Collection (WoSCC) database, specifically the Science Citation Index Expanded (SCI-Expanded). The search was restricted to English-language articles and reviews published between January 2000 and December 2022. Data retrieval, screening, and analysis were conducted in June 2023.ResultsA total of 323 publications were identified, demonstrating annual fluctuations in research output. The United States dominated HBOT-related stroke research in both publication volume and scientific impact. Shai Efrati emerged as the most prolific author in this field, while the Sackler Faculty of Medicine at Tel Aviv University was the most influential institution. The journal Stroke published the highest number of HBOT-related stroke studies. Co-citation analysis revealed “cognitive function” as the primary research focus in HBOT applications for stroke.ConclusionThis bibliometric analysis investigated the current research landscape, trends, and emerging priorities in hyperbaric oxygen therapy (HBOT) applications for stroke. The primary research focus centered on HBOT's therapeutic potential for cognitive function enhancement and chronic-phase post-stroke treatment.